2021
DOI: 10.1002/elps.202100029
|View full text |Cite
|
Sign up to set email alerts
|

Sheath‐assisted versus sheathless dielectrophoretic particle separation

Abstract: Lab‐on‐chip devices are widely being used for binary and ternary cell/particle separation applications. Among the lab‐on‐chip methods, dielectrophoresis (DEP) is a cost‐effective and label‐free method, with great capabilities for size‐based separation of cells and particles, which is mostly performed in sheath‐assisted forms. However, the elimination of the sheath flows offers advantages such as ease of operation and higher sample throughput. In this work, we present a comparison of sheath‐assisted and sheathl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…They also simulated the continuous separation of three groups of bio-particles, including platelets, red blood cells (RBC), and white blood cells (WBC). Dalili and Hoorfar 35 investigated the performance of sheath-assisted and sheathless microfluidic devices containing planar angled electrode arrays to separate three different populations of polystyrene particles according to their size (5, 10, and 15 μm). The results showed that the sheathless design could achieve the highest throughput while the weak sheath-assisted design could achieve the highest yield and purity.…”
Section: Introductionmentioning
confidence: 99%
“…They also simulated the continuous separation of three groups of bio-particles, including platelets, red blood cells (RBC), and white blood cells (WBC). Dalili and Hoorfar 35 investigated the performance of sheath-assisted and sheathless microfluidic devices containing planar angled electrode arrays to separate three different populations of polystyrene particles according to their size (5, 10, and 15 μm). The results showed that the sheathless design could achieve the highest throughput while the weak sheath-assisted design could achieve the highest yield and purity.…”
Section: Introductionmentioning
confidence: 99%